(untitled) (XXI Century. Spanish Literature and Culture, 2004)
The excuses of intellectual shallowness, fake orthodoxy, playing the victim and violence, heterodoxy, ecstasy- literal and metaphorical- of the age in which one lives… these are all the unknowns that play a part in the task of clearing the X of the so called ‘generation X’, whose result is the assumption that it is a group of young narrators who take advantage of the violent, aggressive and rough part of language to express themselves.